Efficacy evaluation and mechanistic investigation of transcutaneous auricular vagus nerve stimulation in enhancing the therapeutic effects of semaglutide and reducing its gastrointestinal side effects: a randomized controlled trial protocol - Tian, Xinyi; Zhang, Lu; Zhang, Kaiqi; Ge, Xiaolei; Luo, Zhengrong; Zhang, Youwen; Wang, Ge; Zhai, Xu (Frontiers in Neurology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a chronic disorder with serious complications. Semaglutide, a GLP-1 receptor agonist, improves glycemic control and weight but is limited by gastrointestinal (GI) side effects, notably nausea, vomiting, and diarrhea, which impair adherence. Transcutaneous auricular vagus nerve stimulation (taVNS), a non-invasive therapy, shows potential in alleviating gastrointestinal symptoms, yet its role in mitigating semaglutide-related side effects and enhancing drug efficacy remains unexplored.MethodsA total of 60 T2DM participants experiencing semaglutide-induced GI side effects will be randomly assigned to a control or intervention group. The control group will receive semaglutide (0.25 mg weekly) plus sham-taVNS, with electrodes attached to the bilateral auricular scapha at 4/20 Hz for 30 min, twice daily. The intervention group will receive semaglutide plus active taVNS, with electrodes on the bilateral cymba and cavum conchae using the same stimulation parameters. Treatment will span two 6-week cycles (12 weeks total). The primary outcome is the Rhodes Index of Nausea, Vomiting, and Retching. Secondary outcomes include gastric electromyography, serological markers, Visual Analogue Scale, and the Simplified Nutritional Appetite Questionnaire. Adverse events will be monitored, and assessments will occur at baseline, week 6, end of treatment, and follow-up.DiscussionThis study aims to determine whether taVNS can alleviate semaglutide-induced GI side effects and enhance the therapeutic efficacy of semaglutide.ConclusionThis study protocol has a randomized, sham-controlled design with rigorous internal validity. Limitations include the potential placebo effects, single-center setting, and small sample size. We expect taVNS to alleviate semaglutide-induced GI side effects and potentially enhance its therapeutic efficacy. In conclusion, this trial will provide preliminary evidence on the safety and effectiveness of taVNS as an supplementary therapy to semaglutide in T2DM, informing the design of future larger-scale studies.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/en-US, identifier ITMCTR2025001226.